Longitudinal choroidal thickness changes among Chinese young adults with various refractive errors - Duan, Fang; Chen, Ziyan; Wang, Zhenyu; Deng, Jiayu; Yeo, Anna C.H.; Yang, Adeline; Drobe, Björn; Wong, Yee Ling; Chen, Xiang (Frontiers in Medicine, 2023)
Purpose To determine the characteristics of longitudinal choroidal thickness (CT) and axial length (AL) changes in a group of Chinese young adults with various refractive errors. Methods In this 2-year prospective cohort study, a total of 291 (314 enrolled at baseline) Chinese medical freshmen aged 18 to 22 years (mean age, 18.7 ± 0.9 years) underwent eye examinations at baseline and follow-up visits, including cycloplegic refraction, ocular biometry measurements, and swept-source optical coherence tomography. Choroidal thickness measurements were performed at nine locations in the macular area. Results At baseline, the CT and AL was significant differences among groups of emmetropia, mild to moderate myopia and high myopia. During a two-year period, there were significant differences found in the changes of the subfoveal CT (P < 0.001) and parafoveal CT of 7 locations between emmetropia and mild to moderate myopia, and the changes of the subfoveal CT (P = 0.002) and parafoveal CT of 6 locations between emmetropia and high myopia. But there were no differences for AL and SE (P > 0.05). The multivariable linear regression analysis showed that baseline subfoveal CT (per 1 um) was a significant factor affecting the changes of subfoveal CT (P < 0.001), whereas age, gender, and baseline AL were not significantly associated. Conclusion The longitudinal change in CT varies with refractive errors in Chinese young adults aged 18 to 22 years over a two-year period. The changes of subfoveal CT were significantly associated with the baseline subfoveal CT, but not associated with baseline AL.